Enhanced efficacy of Magnolia denudata essential oil in fish anesthesia using nanoemulsions and self-microemulsifying drug delivery systems - Zeng, Xiangbing; Dong, Hongbiao; Zheng, Xiaoting; Zhang, Jiasong (Frontiers in Veterinary Science, 2024)
IntroductionThe use of plant essential oils as anesthetics for fish has gained increasing attention, but ethanol, often used as a co-solvent, presents certain limitations. Recently, Magnolia denudata essential oil (MDO) has emerged as a promising alternative for fish anesthesia and sedation.Methods and resultsTo further improve MDO anesthesia efficacy, this study developed nanoemulsion (NE) and self-microemulsifying drug delivery system (SMEDDS) formulations of MDO. Transmission electron microscopy and stability tests confirmed that both NE and SMEDDS possess smaller particle sizes and are stable under various temperature conditions. Anesthetic trials on fish demonstrated that these formulations reduced the time needed to induce anesthesia compared with the non-formulations. Additionally, physiological assessments of the fish gills showed that neither NE nor SMEDDS caused irreversible damage to respiratory function.DiscussionOverall, NE and SMEDDS present a safe and effective delivery system for MDO, enhancing its anesthetic properties while minimizing potential harm to aquatic organisms compared to traditional methods.